Research of the main electromagnetic parameters during the operation of an AC charging station for electric vehicles - Hnatov, Andrii; Arhun, Shchasiana; Sokhin, Pavlo; Ulianets, Olha; Гнатов, Андрій Вікторович; Аргун, Щасяна Валіковна; Сохін, Павло Андрійович; Ульянець, Ольга Анатоліївна (Харківський національний автомобільно-дорожній університет, 2024)
Problem. The increasing popularity of electric cars worldwide is also seen in Ukraine, leading to a growing need for more charging stations. Studies show that 80% of electric car charging happens at home. This home charging usually occurs either through the standard AC power grid or through dedicated AC charging stations. This raises concerns about the safety of these charging stations and their potential interference with other electrical and electronic devices nearby. Goal. The goal of this work is to determine the main electromagnetic parameters in the connection cable during the operation of an AC electric vehicle charging station. Methodology. To achieve this goal, it is necessary to study the electromagnetic parameters of the charging station connection cable when AC flows through it and to identify the electromagnetic parameters of the interference that occurs during the operation of the AC charging station. Classical electrophysical methods for calculating electric and magnetic fields and methods for determining the parameters of quadrupoles from the theoretical foundations of electrical engineering are used. Results. The main electromagnetic parameters in the connection cable during the operation of the AC electric vehicle charging station have been identified. Formulas for calculating the current strength and magnetic field strength have been obtained. Originality. New formulas for calculating the electromotive force of interference generated during the operation of the electric vehicle charging station, when AC flows through the charging cable, have been developed. Parameters of capacitive and magnetic coupling between two conductors in a common bundle have been identified. Formulas for determining the current induced by these parasitic connections have been obtained. Practical value. Accurately determining and calculating these parameters allows for the design of a charging station that operates reliably over a long period without causing interference with nearby electrical and electronic systems or devices.
Дослідження основних електромагнітних параметрів при роботі зарядної станції змінного струму для електромобілів
Keywords: energy source; charging station; electric car; energy efficiency; traction battery; electromotive force; solar panels; capacitive coupling; magnetic coupling; джерело енергії; зарядна станція; електромобіль; енергоефективність; тягова батарея; електрорушійна сила; сонячні панелі; ємнісний зв’язок; магнітний зв’язок; 629.331; 10.30977/AT.2219-8342.2024.54.0.05